2011
DOI: 10.1089/ten.tea.2010.0661
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hypoxia and Fibrinogen Variants on the Expansion and Differentiation of Adipose Tissue-Derived Mesenchymal Stem Cells

Abstract: Upon implantation of tissue-engineered scaffolds, hypoxia will occur until neovascularization takes place. In vivo, the temporary fibrin matrix forms a suitable matrix for this process and fibrin variants can influence the extent of neovascularization. In this study, the influence of oxygen tension and naturally occurring fibrinogen variants on adipose tissue-derived mesenchymal stem cell (ASC) expansion and differentiation were determined. ASC proliferated 1.7-fold faster in 1% oxygen and showed reduced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 35 publications
7
54
1
Order By: Relevance
“…In particular, the proliferation and CFU potency of hBMSCs expanded under hypoxia were not increased compared to those observed under normoxia. Several researchers have demonstrated that hypoxia enhances the in vitro expansion rate [23,24]; however, there are other studies with similar findings to those presented here, such as an O 2 concentration of 1% or less appearing to reduce the proliferation of MSCs [25]. Within the scope of the present experiments, it was assumed that a very low oxygen level can suppress the proliferation and CFU potency of hBMSCs; these tendencies, and their discrepancy with the results of several previous studies, may be related to the effect of the hypoxic condition on cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the proliferation and CFU potency of hBMSCs expanded under hypoxia were not increased compared to those observed under normoxia. Several researchers have demonstrated that hypoxia enhances the in vitro expansion rate [23,24]; however, there are other studies with similar findings to those presented here, such as an O 2 concentration of 1% or less appearing to reduce the proliferation of MSCs [25]. Within the scope of the present experiments, it was assumed that a very low oxygen level can suppress the proliferation and CFU potency of hBMSCs; these tendencies, and their discrepancy with the results of several previous studies, may be related to the effect of the hypoxic condition on cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Within the scope of the present experiments, it was assumed that a very low oxygen level can suppress the proliferation and CFU potency of hBMSCs; these tendencies, and their discrepancy with the results of several previous studies, may be related to the effect of the hypoxic condition on cellular senescence. Cellular proliferation could be reduced at early passages, but the pattern might be reversed in cells at later passages (long-term culture) [23,24]. Cells cultured in a hypoxic condition showed decreased expression of apoptosis/ senescence-related genes [Apo1 (apoptosis antigen-1, also known as the FAS receptor) and p21 (regulator of cell cycle progression at the G1 and S phases; functions in cellular growth arrest)], and the proliferative potential could be maintained even in long-term culture passages.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture under hypoxic conditions was performed as described previously [16]. In brief, MVEC were first stimulated with 10 ng/ml vascular endothelial growth factor (VEGF; Invitrogen) for 24 h. Subsequently, both MVEC and HUVEC were cultured for 24 h in 1% O 2 , 5% CO 2 and 37Ā°C inside a custom-designed hypoxic workstation (T.C.P.S.).…”
Section: Methodsmentioning
confidence: 99%
“…Since oxygen has a limited diffusion capacity in which it can only supply cells within a close proximity to a functional capillary bed, such an increase in adipocyte area creates a hypoxic environment in obese adipose tissue (58,(185)(186)(187). Hypoxic conditions have been shown to inhibit adipogenic differentiation of mesenchymal stem cells (MSCs) from bone marrow and adipose tissue (188)(189)(190)(191). Hypoxia also has an effect on the endocrine function of adipose tissue, suppressing production of adiponectin by adipocytes (185,186,192,193).…”
Section: Introductionmentioning
confidence: 99%